Neolithic "cooperatives": Assessing supra-household cooperation in crop production at Çatalhöyük and beyond - Bogaard, AM (Ex Oriente, 2017)
Interpretation of early established farming communities as assemblies of economically independent units was originally advanced in the absence of detailed evidence for crop handling and land management. The growing availability of such evidence provides an opportunity to revisit this key inference. Here I review expected correlates for different forms of supra-household cooperation in crop production, and turn to the case of Çatalhöyük to assess the implications of the evidence currently available. Residues of crop handling across a series of buildings point clearly to the salience of co-residential households as contexts not only of storage but also of processing and consumption. Nevertheless, current evidence for use of the local alluvial landscape strongly suggests that variable land quality and access to equitable land holdings were paramount concerns for Çatalhöyük cultivators, demanding supra-household coordination and likely shaping its segmented social morphology. Coordinated farming is also suggested by new evidence of crop growing conditions at the very different site and setting of M-LPPNB ‘Ain Ghazal in southern Jordan. This discussion supports the argument that regional trajectories within the western Asian agricultural transition variously chart the gradual emergence of a truly domestic mode of production.